The central role of aquaporins in the pathophysiology of ischemic stroke - Vella, Jasmine; Zammit, Christian; Di Giovanni, Giuseppe; Muscat, Richard; Valentino, Mario (Frontiers in Cellular Neuroscience, 2015)
Stroke is a complex and devastating neurological condition with limited treatment options. Brain edema is a serious complication of ischemic stroke and early edema formation can significantly contribute to infarct formation and thus represents a promising target. Aquaporin (AQP) water channels are contributors to water homeostasis by facilitating or impeding water transport and are consequently implicated in several disease pathways. At least 7 subtypes have been identified in the rodent brain and the use of transgenic mice has greatly aided our current understanding of the roles of these channels. AQP4, the most abundant channel in the brain is upregulated around the peri-infarct border in transient cerebral ischemia and AQP4 knockout mice demonstrate significantly reduced cerebral edema and improved neurological outcome. In models of vasogenic edema, brain swelling is more pronounced in AQP4 null mice than wildtype, providing strong evidence of the dual role of AQP4 in the formation and resolution of both vasogenic and cytotoxic edema. AQP4 is co-localized with inwardly rectifying K+ channels (Kir4.1) and glial K+ uptake is attenuated in AQP4 knockout mice compared to wildtype, indicating some form of functional interaction. AQP4-null mice also exhibit reduction in calcium signaling, suggesting that this channel may also be involved in triggering pathological downstream signaling events. Associations with gap junction protein Cx43 possibly reiterate its role in edema dissipation within the astroglial syncytium. Other roles ascribed to AQP4 include facilitation of astrocytic migration, glial scar formation, modulation of inflammation and signaling functions. Treatment of ischemic cerebral edema is based on the various mechanisms in which fluid content in different brain compartments can be modified. The identification of modulators and inhibitors of AQP4 offer new therapeutic avenues in the hope of reducing the extent of morbidity and mortality in stroke.